GAMBARAN KARIES GIGI ANAK NELAYAN USIA 12 TAHUN DI DUSUN PABEAN, DESA SANGSIT, KABUPATEN BULELENG TAHUN 2013 - I Made Karmawan Putra; I Nyoman Gejir; Ni Made Widhiasti (Jurnal Kesehatan Gigi (Dental Health Journal), 2014)
Background : The prevention of dental carries can be done by the opplication of topical fluor which is a safe methode of prevention. The substance of the application which brings good result is Calsium Fluoride (CaF2). "Teri Jengki "(Ephorus Insularis) contains calsium and fluor in the forms of CaF2 with adequate concentration. The objective of this study is to know the description of carries in fishermen's children in Pabean sub  village of Sangsitt District, Buleleng Regency in 2013. Metode : The study is descriptive with observational design. This study did not use any sample but use s total population of 37 fishermen's children in Pabean sub village of Sangsit District, Buleleng Regency in 2013. Result : Children who didn't have caries are 70,27%, only 29.27% suffered from carries. At an cvarage, the carries in fshermen's children in Pabean sub village of Sangsit District, Buleleng Regency in 2013 is at 0.8. Based on the sexes, the dental carries in male children is at 0.73 and in female children is at 1.00. Conclution : Majority offishermen's children in Pabean sub village of Sangsit District, Buleleng Regency in 2013 are free from dental carries. The avarage of dental carries is lower that the national target and the overage of dental carries in female children is higher than in male children.Keyw ords : dental carri e s, fi shermen, " terii jengki " (Ephorus Insularis)